Dragonbreath: The Frozen Menace #11 - Vernon, Ursula (New York, NY : Dial Books for Young Readers, 2016)
"Danny Dragonbreath travels to the farthest North to find a way to relight his fire before it's too late"--
Keywords: Dragons -- Juvenile fiction; Adventure stories; Dragons -- Fiction; Adventure and adventurers -- Fiction; Humorous Stories